IDENTIFIKASI DAN ANALISIS GINI RATIO KABUPATEN GORONTALO - Harijono Imbran (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2018)
This study aims to analyze and identify the level of income inequality using the Gini Ratio approach. The data sources used in this study are primary and secondary data obtained  through  observation  and  data  collection  reports  both  from  Gorontalo District  Statistic  Center  (BPS)  and  Gorontalo  District  Regional  Development Planning Agency (BAPPEDA), such as Districts in Figures and Indicators of Welfare Results National Census. Data sourced from Bappeda and BPS in the form of per capita Gross Regional Domestic Product data on the basis of Constant Prices, and data  on  consumption  per capita  average.  The  results of  the  study  show  that  the Gorontalo Regency Gini Ratio in the period 2012 - 2017 is in the moderate range (> 0.4) or at moderate or moderate levels.Keywords: Identification, Analysis, Gini Ratio